Conventional and Accelerated “epi-off” Corneal Crosslinking-UVA Procedure in the Treatment of Progressive Keratoconus - Cristina Ariadna Nicula; Dorin Nicula; Anca Maria Rednik; Adriana Elena Bulboaca (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Keratoconus (KCN) is a bilateral ectatic corneal disorder, frequently asymmetric, with progressive thinning of cornea resulting in protrusion, progressive irregular astigmatism, and visual deterioration. An early detection of KCN by using the topographical and tomographical evaluation of Pentacam device is of major importance. Corneal collagen cross-linking (CXL) is the standard procedure for KCN therapy. The final effect of CXL technique is the strengthening of the cornea, with the goal to slow down or arrest the progression of KCN, thus avoiding, or at least delaying the necessity of keratoplasty. CXL is a promising procedure with low risk profil. It is known that the conventional “epi-off” cross-linking has a long-term efficacy in stabilizing progressive KCN. Lately, an accelerated “epi-off” CXL procedure was introduced. We concluded that both standard and accelerated “epi-off” procedures are efficient and safe, resulting in a stabilization of keratoconus.